Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/j.pain.0000000000001749
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of pregabalin preclinical studies

Abstract: Despite large efforts to test analgesics in animal models, only a handful of new pain drugs have shown efficacy in patients. Here, we report a systematic review and meta-analysis of preclinical studies of the commercially successful drug pregabalin. Our primary objective was to describe design characteristics and outcomes of studies testing the efficacy of pregabalin in behavioral models of pain. Secondarily, we examined the relationship between design characteristics and effect sizes. We queried MEDLINE, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
2
14
2
Order By: Relevance
“…Pregabalin is a structural analog of the inhibitory neurotransmitter gammaaminobutyric acid and the main treatment for neuropathic pain. Its analgesic effect differs from that of other analgesics, including morphine, 7 nonsteroidal antiinflammatory drugs, 8 and morphine-like drugs. 9 Previous studies showed that pregabalin could downregulate visceral hyperalgesia, in addition to reducing the severity of basic pain.…”
Section: Introductionmentioning
confidence: 95%
“…Pregabalin is a structural analog of the inhibitory neurotransmitter gammaaminobutyric acid and the main treatment for neuropathic pain. Its analgesic effect differs from that of other analgesics, including morphine, 7 nonsteroidal antiinflammatory drugs, 8 and morphine-like drugs. 9 Previous studies showed that pregabalin could downregulate visceral hyperalgesia, in addition to reducing the severity of basic pain.…”
Section: Introductionmentioning
confidence: 95%
“… 4 By contrast, such treatments are highly effective in preclinical experiments. For example, a recent meta-analysis of all pregabalin experiments in rodents showed an average analgesic response of 71% of the maximum possible effect (such that the majority of animals demonstrated a >50% decrease in pain), 3 whereas clinically pregabalin has a number needed-to-treat of 4.5 against neuropathic pain (such that less than 25% of patients who would not have responded to placebo would show a >50% decrease in pain). 4 It has never been directly evaluated whether part of the reason for this arguably poor translation lies with organismic factors such as age or duration of injury before the analgesic is administered.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be recognized that our current study only used young male mice, many pain phenotypes differ between sexes with females typically reporting greater pain responses 32,33 . A further limitation of our study regards translating efficacy from a single pain model in one mouse strain to humans; for example, pregabalin has larger and broader analgesic effects in rodent chronic pain models than observed clinically 34 .…”
Section: Discussionmentioning
confidence: 99%